Socialization of Building Business Organizational Culture Towards Sustainability in Culinary Business in Sukakarya District, Sabang City - Atika Aini Nasution; Baginda Harahap; Raflis; Roy Nuary Singarimbun; Neni Sri Wahyuni; Selvi Aristantya (IJCS: International Journal of Community Service, 2023)
This Community Service should be able to contribute to culinary business Aguan Peanut Cake actors in the Sukakarya sub-district, Sabang City. A strong culture and good management of Human Resources are tools to compete with competitors in an organization. The result of a strong culture is that the culture will promote consistent behavior that can create organizational effectiveness that is influenced by employee performance. But if the culture is not good, then the goal will go in the wrong direction. There are 4 factors in the development of Organizational Culture, namely a culture of discipline, honesty and responsibility, a creative work culture, an environmentally friendly work culture and a work culture that is aware of local values. Changes in the organizational culture need to be disseminated to all employees so that it becomes a daily work behavior, so that the organizational culture becomes a collective awareness that can benefit all parties. However, it is not easy to create a new habit, it needs simultaneous and continuous encouragement and effort so that the organizational culture becomes a positive habit.